2021
DOI: 10.1016/j.nicl.2021.102776
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight is associated with brain tissue volumes seven decades later but not with MRI markers of brain ageing

Abstract: Highlights Larger birth weight is associated with larger brain tissue volumes at age 73. Birth weight is not associated with age-associated brain features. Effect of birth weight on brain volumes is independent of overall body size. Early life growth is likely to confer brain tissue reserve in later life.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Low birth weight relative to birth length has been shown to be associated with lower brain volumes at 75 as well as reduced processing speed and executive function ( Muller et al, 2014 ). A recent study among elderly in their early seventies demonstrated that birth weight was positively associated with total brain volume and regional cortical surface area amongst others, which could be explained by larger intracranial volume, rather than by age-related tissue atrophy ( Wheater et al, 2021 ).…”
Section: Early Life Factors and Markers Of Brain Reservementioning
confidence: 99%
“…Low birth weight relative to birth length has been shown to be associated with lower brain volumes at 75 as well as reduced processing speed and executive function ( Muller et al, 2014 ). A recent study among elderly in their early seventies demonstrated that birth weight was positively associated with total brain volume and regional cortical surface area amongst others, which could be explained by larger intracranial volume, rather than by age-related tissue atrophy ( Wheater et al, 2021 ).…”
Section: Early Life Factors and Markers Of Brain Reservementioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 2, 2022. ; https://doi.org/10.1101/2022.12.02.514196 doi: bioRxiv preprint birthweights. Given previous findings of broad effects of BW on cortical area and volume (5,6,16), we did not expect effects to be localized. Rather, we expected BW to affect gross head and brain size irrespective of sex, but we also performed supplementary analyses controlling for intracranial volume (ICV) in order to check for possible specificity of effects.…”
Section: Samplesmentioning
confidence: 99%
“…Finally, models were rerun only including participants with birth weights between 2.5 and 5.0 kg, to assess whether relationships were upheld also when excluding low and high birthweights. Given previous findings of broad effects of BW on cortical area and volume (5,6,16), we did not expect effects to be localized. Rather, we expected BW to affect gross head and brain size irrespective of sex, but we also performed supplementary analyses controlling for intracranial volume (ICV) in order to check for possible specificity of effects.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebrospinal fluid, grey matter, white matter, and white matter hyperintensities were segmented using FreeSurfer (Fischl, 2012), FSL-FAST (Zhang et al, 2001), and a semi-automated multi-spectral fusion method, which capitalised on multimodal information provided by T2-w, T1-w, T2*-w and FLAIR MRI sequences (Valdés Hernández et al, 2010;Wardlaw et al, 2011;Wheater et al, 2021). The normal-appearing white matter was defined as regions of the white matter where no white matter hyperintensity was identified.…”
Section: Segmentation Of Regions Of Interest In the Study Of Referencementioning
confidence: 99%